Successful approach for integrated farming system - Ranade, D H; Bhagat, D V; Girothia, O P; Jadav, M L (Indian Farming, 2020)
Team of scientists from All India Coordinated Research Project for Dryland Agriculture, College of Agriculture, Indore regularly visits different rural areas for convincing and motivating the farmers for adopting improved rainfed technologies for enhancing their farm production and income. During a visit to Dhar district of Malwa and Nimar region, the team came across few progressive farmers who are practicing various agricultural methods on basis of their own field experiences for earning profits from farming. However, due to lack of extension activities and awareness, other farmers are not getting information on these very successful and efficient farming practices. Experience gathered by the team through interaction with progressive farmer is detailed here for its wide scale adoption.